Differentiation of honey produced in two PDO regions in Portugal using FTIRT-ATR analysis - Pedro, Soraia (2024)
The chemical composition of honey in a Protected Designation of Origin (PDO) reflectes the unique characteristics of the region, ensuring authenticity through rigorous standards. To identify the consistent analytical parameters within a particular PDO and assess the possibility of distinguishing them using rapid techniques, such as FTIR-ATF (Fourier Transform Infrared Spectroscopy with Attenuated Total Reflectance).